Millimeter wave beam steering reflectarray antenna based on mechanical rotation of array - Abbasi, Muhammad Inam; Jamaluddin, Mohd Haizal; Seman, Norhudah; Dahri, Muhammad Hashim; Kamarudin, Muhammad Ramlee; Sulaiman, Noor Hafizah (Institute of Electrical and Electronics Engineers Inc., 2019)
This work provides design and analysis of a beam steering reflectarray antenna, designed at 26 GHz, based on the mechanical rotation of the array. Unit cells based on circular ring elements are designed, and scattering parameter measurements have been carried out for obtaining progressive phase distribution. The unit cell measurements demonstrated a maximum reflection loss of 4 dB with a total phase range of almost 360°. Symmetricity of the array and the resonant elements has been exposed to steer the main beam by tilting the reflectarray at different angles. A beam steering range of more than ±60° has been demonstrated by varying the tilt angle from +30°to -30°. The designed 20 × 20 element array provided a maximum gain of 26.47 dB at 0° which reduced to 19.8 dB at 61.9° in the elevation plane. On the other hand, the reflectarray antenna demonstrated a maximum bandwidth of 13.1% with a minimum side lobe level of -25.9 dB.